PENURUNAN KUALITAS TIDUR PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH PENDERITA RHINITIS ALERGIKA - Triansyah, Irwan; Putri, Shyntia Peratami; Rosmaini; Vani, Ade Teti (Nusantara Hasana Journal, 2024)
Allergic rhinitis (RA) is an inflammatory disease of the nasal cavity that occurs after exposure to allergens mediated by Ig E, causing symptoms of repeated sneezing, rhinorrhea, itching and nasal congestion, and watery eyes. Congestion in the nose and sinus drainage will make it difficult for sufferers to sleep. Allergic rhinitis can affect the quality of sleep sufferers. The Type of this research is analytic observational study with cross sectional design. Population affordable of this research was all of the Medical Faculty students of Baiturrahmah University Class 2019 as many as 145 people with taking sample use technique simple random sampling. Data analysis used univariate analysis is presented in the form of distribution frequency and analysis bivariate use test spearman rho. There are 88 students or 60,7 % of students of the Faculty of Medicine, Baiturrahmah University Batch 2019 suffered from allergic rhinitis of all students, with the most allergic rhinitis were women as many as 30 students (36.6%). The most common clinical symptom was sneezing, which were 76 students (86.4%). There were 2 students with allergic rhinitis with good sleep quality (2.4%) and allergic rhinitis with bad quality of sleep obtained as many as 39 students (47.6%). Based on the analysis of the hypothesis test, the p-value was 0.000 (p>0.05), r=0,597, dan OR =30,469. There is relation between allergic rhinitis and quality of sleep of Medical Faculty students of Baiturrahmah University Class 2019. Conclusions: Medical Faculty students of Baiturrahmah University Class 2019 suffering from allergic rhinitis experience decrease sleep quality.